2021
DOI: 10.1126/science.aay1513
|View full text |Cite
|
Sign up to set email alerts
|

Echolocation in soft-furred tree mice

Abstract: Echolocation is the use of reflected sound to sense features of the environment. Here, we show that soft-furred tree mice (Typhlomys) echolocate based on multiple independent lines of evidence. Behavioral experiments show that these mice can locate and avoid obstacles in darkness using hearing and ultrasonic pulses. The proximal portion of their stylohyal bone fuses with the tympanic bone, a form previously only seen in laryngeally echolocating bats. Further, we found convergence of hearing-related genes acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 65 publications
0
31
0
1
Order By: Relevance
“…As such, future studies will be required to test for the possible use of auditory cues in stabilizing HD cell tuning in blind mice, though previous work in blindfolded rats suggests that auditory cues do not exert a strong effect on HD cell tuning 31 . However, it should be noted that a recent study found that some mice can echolocate 53 .…”
Section: Discussionmentioning
confidence: 94%
“…As such, future studies will be required to test for the possible use of auditory cues in stabilizing HD cell tuning in blind mice, though previous work in blindfolded rats suggests that auditory cues do not exert a strong effect on HD cell tuning 31 . However, it should be noted that a recent study found that some mice can echolocate 53 .…”
Section: Discussionmentioning
confidence: 94%
“…In 1944, Griffin [15] successfully recorded the ultrasound emitted by bats, and named the process of acquiring information about the surrounding environment by bats emitting ultrasound as echolocation. At present, related studies have found that in addition to bats, the rodents of the genus Typhlomys [16], toothed whales [17], and birds [18] all have echolocation capability. Bat echolocation has multiple functions, such as target detection, information exchange, and environment recognition [19].…”
Section: Echolocation and Obstacle Avoidancementioning
confidence: 95%
“…Echolocation is an adaptive and perceptive behavior for obstacle avoidance, orientation, and hunting, which involves emitting sounds into the environment and listening to the echoes returning from objects ( Jones, 2005 ). Although echolocation occurred in several mammalian lineages ( He et al., 2021 ), its origin and elaboration have been widely studied only in bats and whales ( Jones, 2005 , 2010 ; Jones and Teeling, 2006 ). In contrast to a single origin of echolocation in the last common ancestor (LCA) of toothed whales supported by fossil records, molecular evolution, and gene functional experiments ( Churchill et al., 2016 ; Geisler et al., 2014 ; Liu et al., 2018 ; Park et al., 2016 ), the evolutionary origin(s) of laryngeal echolocation in bats remain contentious ( Jones and Teeling, 2006 ; Nojiri et al., 2021 ; Wang et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%